Intracameral Bevacizumab versus Subconjunctival Bevacizumab in the Treatment of Neovascular Glaucoma - Sultan, Sharjeel; Siyal, Nisar; Waris, Nazish; Khokhar, Rasheed (Pakistan Journal of Ophthalmology, 2020)
Purpose: To compare the effect of intracameral Bevacizumab with sub-conjunctival Bevacizumab in the treatment of neovascular glaucoma. Study Design: Quasi Experimental study. Place and Duration of Study: This study was conducted at Civil hospital Karachi, Pakistan from September 2017 to October 2018. Material and Methods: Patients with intractable Neo-vascular glaucoma visiting the outpatient department of civil hospital, Karachi were included in the study and followed up for 8 months. Patients with sulcus or scleral fixation IOLs and those who were treated with vitreoretinal surgeries were excluded. Patients were divided into two groups. Group A included patients treated with intracameral Bevacizumab and in group B, patients treated with sub-conjunctival Bevacizumab were included. Best-corrected visual acuity (BCVA), intraocular pressure (IOP) and neovascularization of the iris (NVI) were compared between the two groups. Results: Thirty-eight eyes were included in the study; 24 (56.7%) right eyes and 14 (43.3%) left eyes. Most of the patients were males with mean age of 54.53 ± 7.2 years. Mean total injection/eye was 3.45 ± 1.73 in group A and 3.12 ± 2.10 in group B. Pre-injection BCVA (log MAR) was 0.48 ± 0.32 in group A and 0.34 ± 0.32 in group B. At 8 months, BCVA was 1.7 ± 0.2 in group A and 0.48 ± 0.34 in group B which were statistically significant. Pre-injection IOP (mmHg) was 48.9 ± 1.8 in group A and 47.34 ± 1.8 in group B. Post-injection IOP was 28.7±0.8 in group A (p = 0.001) and 34.2 ± 3.4 in group B (p = 0.11) at eight months. Conclusion: This study demonstrates that intracameral Bevacizumab significantly improves BCVA and controls IOP in neovascular glaucoma. However, sub-conjunctival Bevacizumab significantly improves BCVA but decrease in IOP is not statistically significant.